Penyelesaian Soal Cerita pada Pembelajaran Matematika dengan Pendekatan Pemecahan Masalah di SDN Inpres Depapre Kabupaten Jayapura - Wasito, Wasito; Ali, Aisyah; Ristiani, Ria (J-Abdimas Cenderawasih, 2023)
This research was conducted at SDN Inpres Depapre Jayapura Regency with the aim of assisting elementary school teachers in solving word problems in learning mathematics using a Problem Solving approach. The subjects in this study were 6 teachers from SDN Inpres Depapre and 3 teachers from SD YPK Amai Depapre. This activity was carried out using the lecture method and direct accompaniment using cooperative learning methods, interactive collaborative between facilitators and elementary school teachers through a comprehensive study of learning. Training activities include giving general explanations from the facilitator then followed by practice activities discussing story problems with Problem Solving, then given the opportunity for teachers to practice solving story problems accompanied by the facilitator. The next stage is reflection and evaluation of the results that have been done. After carrying out this training activity, the training participants (teachers of SDN Inpres Depapre, Jayapura Regency) were very motivated and enthusiastic in developing their ability to solve math problems by applying a Problem Solving approach.